(untitled) (Medical Forum Monthly, 2024)
Objective: To describe postoperative complications in Lichtenstein repair under spinal anesthesia. Study Design: Descriptive, prospective, cohort study Place and Duration of Study: This study was conducted at the Abbasi Shaheed Hospital, Karachi for six months duration from 07.02.2023 till 06.08.2023. Methods: It is a descriptive, prospective1, cohort study with both qualitative and quantitative aspects.my research is focus on postoperative complications occurs after Lichtenstein repair. Sample size was derived from formula2 and through internet based calculator.net which is 194.The no of participants selected through consecutive method of sampling and follow ups are done postoperatively in wards and on out-patient department bases. The postoperative complications were taken as variables and analysed through SPSS. The patients are between 21 and 85 years old. We categorized the individuals into two distinct groups F1and F2. In the F1 group, we used the European hernia society classification (EHS), and in the F2 group, we used ultrasound and the EHS classification to determine accurate defect size. Lichtenstein repair is the procedure of choice. Postoperative complications were evaluated. Results: According to our results, we found that out of the 97/194 patients in the F1 group, 51 have lateral inguinal hernia and 41 have medial inguinal hernia. In the F2 group, 43 patients have lateral inguinal hernia, and 49 patients have medial inguinal hernia. Postoperative complications. In our study, many patients who developed complications had Lichtenstein repair done by postgraduate surgeons under supervision and surgical registrars. Experienced surgeons like Professor and Associate Professor have performed Lichtenstein repairs on patients with negligible or fewer complications. Conclusion: Accurate estimation of defect size, adequate spinal anesthesia with experienced anesthetists, proper fixation and overlapping of mesh, proper suture material, and instruments with proper lightning and sterilization techniques—surgical experience noted >300 lichtenstein repairs can reduce postoperative complications in Lichtenstein repair.